show that the limit as h approaches zero of ((cosh-1)/h) = 0.
*The bold numbers preceding each line are simply line numbers, they are not apart of the equations.*
1 lim (as h approaches 0) of ((cosh - 1)/h)
2 = lim (as h approaches 0) of -((2sin2(h/2))/h)
3 = -lim as theta approaches zero of ((sin[tex]\Theta[/tex]/[tex]\Theta[/tex])*sin[tex]\Theta[/tex]
4 = -(1)(0)
5 = 0
I'm confused as to how the author of the text was able to get from line 1 to line 2. If someone could workout the steps between these two lines I would be appreciative. I'm drawing a blank here!